2017
DOI: 10.15406/mojgg.2017.01.00026
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Mass Index and Chronic Non-Communicable Diseases among the Elderly

Abstract: The associations between a high body mass index (BMI) related to overweight/obesity and the increase in the incidence of NCD's in the elderly population becomes increasingly evident 16 The quality of nutritional intake, one of the underlying aspects of malnutrition in the elderly and low levels of physical activity, for example, appears to be associated with weight gain, with multimorbidities and it also seems to be strongly related to low socioeconomic status.17 Furthermore, susceptibility to the contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In exploring the association between BMI and multimorbidity, previous studies reported different findings for males and females. For example, a study in older adults showed significant differences between genders in the estimates of NCDs and in the association between NCDs, multimorbidity and BMI [ 16 ]. However, another study in Serbian adults did not support the gender differences [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In exploring the association between BMI and multimorbidity, previous studies reported different findings for males and females. For example, a study in older adults showed significant differences between genders in the estimates of NCDs and in the association between NCDs, multimorbidity and BMI [ 16 ]. However, another study in Serbian adults did not support the gender differences [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figures generated indicated that all mean anthropometric measures were towards higher sides both in men and women. Evidences reported the association of extended anthropometry measurements with hypertension [20,21], cardiovascular risk and metabolic syndromes [22][23][24], heart failure [25,26] and diabetes [26,27]. A WHO expert consultation [14] reviewed scientific evidence that suggested Asian populations have different associations between BMI, percentage of body fat, and health risks than do European populations.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Diabetes Mellitus is associated with genetic influences, population aging, quality of life, diet, obesity and many other elements. Among these, the aspects related to the adoption of a sedentary lifestyle are the main causes of this pathology 3,4 .…”
Section: Introductionmentioning
confidence: 99%